Schema Therapy and Depressive Disorder: A systematic review (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Schema therapy (ST) has been gaining evidence beyond personality disorders, but research into some conditions such as depression is still in its initial stages. The aim of this review was to indicate in the literature the main results of primary research into the treatment of depression from a ST perspective. A systematic review was conducted using PubMed, ScienceDirect, and APA PsycInfo databases, encompassing articles up until October 7, 2023. Seven studies met the criteria and were selected for full analysis. The results showed efficacy of ST for treating depression in all studies. ST showed similar results when compared to Cognitive Behavioral Therapy and Acceptance and Commitment Therapy. These results reinforce the need to create specific protocols for chronic depression using ST, in order to find forms of treatment that can be effective and stable over time for a large number of patients.
Keywords: dysthymic disorder; schema therapy; major depressive disorder; persistent depressive disorder; cognitive behavior therapy